1997
DOI: 10.1128/jb.179.7.2289-2299.1997
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a large Borrelia burgdorferi motility operon which is initiated by a consensus sigma70 promoter

Abstract: A large motility operon, referred to as the flgB operon, was identified, characterized, and mapped at 310 to 320 kb on the linear chromosome of the spirochete Borrelia burgdorferi. This is the first report that a The bacterial motility apparatus is a highly organized but complicated structure composed of the flagellar filament, the hook-basal body complex, membrane-associated energy-transducing components, and proteins involved in export (1, 49, 69). Most of the flagellar genes of Escherichia coli and Salmonel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
111
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(118 citation statements)
references
References 65 publications
7
111
0
Order By: Relevance
“…3a). The flagellum assembly protein FliI (22,45) and the motor protein FliM (63) were present at similar levels in the wild type and SC-E1, while the level of MotB, which is part of the flagellar stator (33), was slightly reduced in SC-E1 compared to the wild type. Taken together, the Western blot analyses indicated that insertion of kan into flgE did not appreciably alter the amounts of proteins encoded by other select motility genes that were located either upstream or downstream of the mutation.…”
Section: Isolation Of the Sc-e1 Mutantmentioning
confidence: 88%
See 3 more Smart Citations
“…3a). The flagellum assembly protein FliI (22,45) and the motor protein FliM (63) were present at similar levels in the wild type and SC-E1, while the level of MotB, which is part of the flagellar stator (33), was slightly reduced in SC-E1 compared to the wild type. Taken together, the Western blot analyses indicated that insertion of kan into flgE did not appreciably alter the amounts of proteins encoded by other select motility genes that were located either upstream or downstream of the mutation.…”
Section: Isolation Of the Sc-e1 Mutantmentioning
confidence: 88%
“…Monoclonal antibodies to FlaB (H9724), FlaA, and DnaK were provided by A. Barbour (University of California, Irvine), B. Johnson (Centers for Disease Control and Prevention, Atlanta, GA), and J. Benach (State University of New York, Stony Brook), respectively. Polyclonal anti-FliI, anti-CheA2, anti-CheX, and anti-CheY3 were described previously (22,37,48). Polyclonal anti-recombinant CheW3 was provided by C. Li (unpublished data).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We overexpressed CsrA Bb (ES25) under the control of a constitutive promoter, P flgB (35), with a C-terminal sixhistidine tag in an lp25-deficient, clonal isolate of B. burgdorferi on May 10, 2018 by guest http://iai.asm.org/ (ML23) by using the borrelial shuttle vector pBSV2 (78). Surprisingly, we found that the colonies on BSK-II agar overlays that grew in the presence of kanamycin (conferred by the shuttle vector) were compact compared to those of the parental strain (data not shown).…”
Section: Downloaded Frommentioning
confidence: 99%